Gingival proliferative lesions in children and adolescents in Brazil: A 15-year-period cross-sectional study - Fabiana Caroline daSilva; Cleto Mariosvaldo Piazzetta; Cassius Carvalho Torres-Pereira; Juliana Lucena Schussel; José Miguel Amenábar (Wolters Kluwer Medknow Publications, 2016)
Background: Studies assessing the prevalence of oral lesions in children and adolescents, particularly in gingiva are scarce in the literature. The aim of the study was to describe the distribution of gingival proliferative lesions based on clinical and histopathological diagnoses in children and adolescents. Materials and Methods: A review of clinical charts of children and adolescents aged between 0 and 18 years old, admitted to the Oral Medicine Outpatient Unit, of Universidade Federal do Paraná, for 15 years (1994-2009) was performed. Results: Six hundred and sixty-nine out of 5,129 patients treated during this period were aged between 0 and 18 years old, and 45 of these had gingival lesions. The largest number of lesions was observed between 11 and 16 years old. The majority of the patients were referred by Curitiba's public health system. Pyogenic granuloma was the most frequent lesion (19 = 42.2%), followed by peripheral giant cell lesion (11 = 24.4%), gingival fibromatosis (10 = 22.2%), and peripheral ossifying fibroma (5 = 11.1%). Conclusion: Gingival proliferative lesions can show similar clinical characteristics. Appropriate clinical and histopathological diagnoses are necessary to guide the healthcare professional to establish the adequate treatment and to estimate the risk of recurrence.